Terapi Aktivitas Kelompok Meronce Terhadap Tingkat Stress Lansia Yang Menjalani Perawatan di Panti Sosial Tresna Werdha Budi Mulia - Adawiyah, Siti Robeatul; Safitri, Alfika; Hambali, Mohamad Jalal; Latif, Mohamad Sohibul; Soleha, Nunu; Sari, Putri Nanda; Pertiwi, Siti Medika Sastika; Muliah, Siti; Mutiara, Siti; Noviasuci, Wulan; Almansyah, Yasa (Kolaborasi: Jurnal Pengabdian Masyarakat, 2025)
Abstract Introduction: The elderly have a gradual physical and psychological decline, where the decline of these conditions can cause stress in some elderly people. Seniors living in assisted living facilities may experience psychological distress. Preventive steps are needed to maintain the mental health of the elderly so that the elderly can have a better quality of life with various activities to improve their cognitive function and affection. The form of intervention is in the form of Group Activity Therapy (TAK), an easy, economical and affordable physical exercise. One of the stress management is to do meronce therapy Objective: To determine the Effect of Activity Therapy Using Meronce on the Stress Level in the Elderly Living in Wisma Manga PSTW Budi Mulia 2. Method: using a DASS questionnaire to measure stress levels in the elderly as many as 10 respondents then meronce group activity therapy was carried out Result: There was a decrease in stress levels in the elderly after group activity therapy was carried out Conclusion: : the achievement of the results of this group activity therapy activity activity showed a decrease in stress levels in the elderly at Wisma Mangga PSTW Budi Mulia 2 Jakarta.